The Mechanism Underlying the Protective Effects of Tannic Acid Against Isoproterenol-Induced Myocardial Fibrosis in Mice - Ma, Donglai; Zheng, Bin; Du, Huiru; Han, Xue; Zhang, Xuan; Zhang, Jianping; Gao, Yonggang; Sun, Shijiang; Chu, Li (Frontiers in Pharmacology, 2020)
Tannic acid (TA) is a class of complex water soluble polyphenolic derivatives, it shows anti-carcinogenic and anti-inflammatory activities and eliminates the body's ability to form hydroxyl radicals. We studied TA’s protective effects against isoproterenol (ISO) -induced myocardial fibrosis (MF) and potential mechanisms in mice. Mice received TA and ISO dosing and were expend after 48 h later.The serum of creatine kinase (CK) and Lactate dehydrogenase (LDH) were detected by ELISA assay. Cardiac histopathology was fulfilled using H&E and Masson's Trichrome dyeing. Immunohistochemical dyeing was applied to indicate changes in B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein (Bax) and basic fibroblast growth factor (bFGF) protein expressions in cardiac tissue. Expressions of atrial and brain natriuretic peptides (ANP and BNP, respectively), c-fos and c-jun mRNA were decided by RT-PCR. Western blotting was used to detect the expressions of nuclear factor-κB (NF-κB) p65, toll-like receptor (TLR4), p38, Bax, Bcl-2 and caspase-3 expressions. Compared against the ISO group, the TA group can be obviously reduced in TLR4, p38, NF-κB (p65), caspase-3, Bax and Bcl-2 proteins, as well as LDH and CK. These results indicated that TA protects against ISO-induced MF, the potential mechanism may be due to its ability to suppress TLR4 mediated NF-κB signaling pathway.